Glam Rock and the society of the spectacle. Issue 2 (3rd April 2021) - Stratton, Jon
ABSTRACT: This article considers Glam Rock in the historical context of the development of the society of the spectacle in the United Kingdom. Glam Rock is usually discussed as a youth culture. This article places Glam Rock in relation to the acceptance of television, especially colour television, the associated importance of advertising and the establishment of the UK as a consumption society. One important aspect of this was the emphasis on fashion. All together, this development is what Guy Debord described as the society of the spectacle. The most important Glam Rockers, Marc Bolan and David Bowie, understood the centrality of colour television and developed images that were enticing to a television audience.